Three-dimensional negative electrode active material, preparation method thereof and all-solid-state lithium ion battery

By using the melting reaction method in a sulfide all-solid lithium-ion battery, a composite negative electrode filled with LixSn-Li2S as a three-dimensional framework and LiySi active material is solved, the battery capacity attenuation and rate performance caused by volume changes in the silicon-based negative electrode during circulation is solved. The poor problem achieves the high-rate performance and cycle stability of the battery.

CN119419235APending Publication Date: 2025-02-11GAO NENG SHI DAI (SHEN ZHEN) XIN NENG YUAN KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411451963.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In existing sulfide all-solid lithium-ion batteries, the silicon-based negative electrode will undergo huge volume changes during the cycle, resulting in rapid attenuation of the battery capacity and uneven contact with the sulfide solid electrolyte, affecting the rate performance of the battery.

Method used

The melt reaction method is used to uniformly assemble silicon, SnS2 and metal lithium to form a composite negative electrode filled with LixSn-Li2S as a three-dimensional framework and LiySi active material. The LixSn-Li2S framework provides active adsorption sites, strain buffer space and fast Li+ transmission path. LiySi, as the main active substance, transmits Li+ through the skeleton, and due to partial lithiation, the volume changes are reduced, so the skeleton can withstand stress changes.

Benefits of technology

It improves the rate performance and cycle stability of the battery, extends the cycle life of the battery, and reduces the mechanical stress of the electrode structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419235A_ABST
    Figure CN119419235A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and particularly discloses a three-dimensional negative electrode active material, a preparation method thereof and an all-solid-state lithium ion battery. Comprising three-dimensional frameworks LixSn-Li2S and LiySi, wherein x is more than or equal to 2 and less than or equal to 4.4, and y is more than or equal to 1 and less than or equal to 4.4; liySi is attached to the three-dimensional framework Li < x > Sn <-> Li < 2 > S. According to the invention, silicon, SnS2 and metal lithium as a reaction bridge are uniformly assembled by using a melting reaction method to form the three-dimensional negative electrode active material which takes LixSn-Li2S as a three-dimensional skeleton and fills the pores of the three-dimensional skeleton with the LiySi active material, and the all-solid-state lithium ion battery assembled by the three-dimensional negative electrode active material has excellent cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a three-dimensional negative electrode active material and a preparation method thereof, and an all-solid-state lithium ion battery. Background Art

[0002] In recent years, the vigorous development of new energy vehicles and portable electronic devices has greatly stimulated the extensive research of high energy density lithium-ion batteries. Among various potential development paths, sulfide all-solid-state batteries have become a hot topic of concern due to their higher energy density, ultra-high safety and easier implementation. The negative electrode material determines the energy density of sulfide all-solid-state batteries. The most common negative electrode materials in sulfide solid-state batteries are indium and indium-lithium alloys; however, the redox potential of indium is ≈0.6V (vs Li+ / Li), high density (7.31g / cm 3 ) and high cost make it challenging to use in industrial applications. Metal lithium and silicon anodes are the two most attractive anode materials because of their ultra-high energy density. Lithium metal anodes will produce serious lithium dendrites during use, which greatly limits their application; silicon anodes have an ultra-high room temperature theoretical specific capacity of 3590mAh / g, which is about ten times that of traditional graphite. However, they will produce huge volume changes (>300%) during the cycle process. The volume expansion will continuously squeeze the surrounding sulfide electrolyte, causing gaps between the two, making it difficult for lithium ions to transfer between the two, partially deactivating the silicon anode, and rapidly decaying the battery capacity. And low conductivity also makes its commercialization challenging.

[0003] In addition, the contact between the silicon-based negative electrode and the sulfide solid electrolyte is solid-solid contact. If the two are not evenly dispersed, it will be difficult for some silicon negative electrodes to directly obtain lithium ions from the sulfide solid electrolyte, which is manifested as poor rate performance of the battery. The silicon negative electrode will also generate huge mechanical stress during the cycle, causing the electrode to break and crush, resulting in a rapid decrease in battery capacity. For this reason, many strategies have been proposed, such as designing nanostructures, interface engineering strategies, and composites with other materials. Among them, nano-sizing plays an important role in improving the cycle stability of silicon negative electrodes, but it cannot make the battery's cycle performance meet commercial requirements; composites with other materials to reduce the specific capacity of the material and thus reduce volume expansion are also important strategies. The silicon-carbon composite materials currently used in liquid batteries are difficult to apply to sulfide all-solid-state batteries, because sulfide solid electrolytes are incompatible with carbon materials, and carbon materials will accelerate the decomposition of sulfide solid electrolytes. Therefore, finding new composite materials is an important development direction for silicon-based negative electrodes of sulfide all-solid-state batteries.

[0004] Therefore, it is necessary to provide a three-dimensional negative electrode active material and a preparation method thereof and an all-solid-state lithium-ion battery to improve the structure of the negative electrode active material, thereby further improving the rate performance and cycle stability of the battery. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a three-dimensional negative electrode active material and a preparation method thereof and an all-solid-state lithium-ion battery to improve the structure of the negative electrode active material, thereby further improving the rate performance and cycle stability of the battery.

[0006] A first aspect of the present invention provides a three-dimensional negative electrode active material.

[0007] Specifically, the three-dimensional framework Li x Sn-Li 2 S and Li y Si, where 2≤x≤4.4, 1≤y≤4.4;

[0008] The Li y Si is attached to the three-dimensional framework Li x Sn-Li 2 S on.

[0009] Preferably, the three-dimensional skeleton Li x Sn-Li 2 S in Li x Sn and Li 2 The mass ratio of S is (1~3):(1~2).

[0010] Further preferably, the three-dimensional skeleton Li x Sn-Li 2 S in Li x Sn and Li 2 The mass ratio of S is (1.49~1.63):1.

[0011] More preferably, the three-dimensional skeleton Li x Sn-Li 2 S in Li x Sn and Li 2 The mass ratio of S is (1.49~1.55):1.

[0012] Preferably, the particle size of the three-dimensional negative electrode active material is 1 to 30 μm, and the specific surface area is 1 to 10 m 2 / g.

[0013] More preferably, the particle size of the three-dimensional negative electrode active material is 24 to 30 μm, and the specific surface area is 4 to 10 m 2 / g.

[0014] More preferably, the particle size of the three-dimensional negative electrode active material is 24-29 μm, and the specific surface area is 4-7 m 2 / g.

[0015] A second aspect of the present invention provides a method for preparing a three-dimensional negative electrode active material.

[0016] Specifically, the following steps are included:

[0017] Lithium metal is melted and liquefied, and SnS is added 2 , stirring, then adding silicon, stirring, cooling and refining to obtain the three-dimensional negative electrode active material.

[0018] Preferably, the SnS 2 The mass ratio to metallic lithium is (1~10):1.

[0019] Further preferably, the SnS 2 The mass ratio to metallic lithium is (1~5):1.

[0020] More preferably, the SnS 2 The mass ratio to metallic lithium is (1.4~3):1.

[0021] Preferably, the silicon and SnS 2 The mass ratio is 1:(0.6~5).

[0022] Further preferably, the silicon and SnS 2 The mass ratio is 1:(0.6~2).

[0023] More preferably, the silicon and SnS 2 The mass ratio is 1:(0.8~1.5).

[0024] Tin disulfide (SnS 2 ) has a high theoretical specific capacity (645 mAh / g), which has a layered hexagonal Cdl 2 type structure, which is conducive to Li + The embedding and extraction of silicon, SnS 2 As well as the uniform assembly of metallic lithium as a reaction bridge, a Li x Sn-Li 2 S is a three-dimensional skeleton, Li y The composite negative electrode is filled with Si active material into its pores, Li x Sn-Li 2 The S skeleton endows the composite anode with abundant active adsorption sites, sufficient strain buffer space and fast Li + Transmission path, Li y Si is the main active material through Li x Sn-Li 2 S skeleton transports Li + , and since it is partially lithiated, Liy The expansion of Si material is greatly reduced, making Li x Sn-Li 2 The S skeleton can withstand its stress changes, so that the electrode exhibits excellent structural stability and the battery exhibits excellent cycle life.

[0025] Preferably, the temperature of the melt liquefaction is 180-580°C.

[0026] More preferably, the temperature of the melt liquefaction is 200-400°C.

[0027] More preferably, the temperature of the melt liquefaction is 300°C.

[0028] Preferably, the particle size of the silicon is 10 to 1000 nm.

[0029] More preferably, the particle size of the silicon is 30 to 200 nm.

[0030] More preferably, the particle size of the silicon is 30 to 100 nm.

[0031] Preferably, the refinement includes at least one of ball milling, grinding and air flow milling.

[0032] A third aspect of the present invention provides a negative electrode.

[0033] Specifically, the negative electrode includes the three-dimensional negative electrode active material provided in the first aspect.

[0034] A fourth aspect of the present invention provides an all-solid-state lithium-ion battery.

[0035] Specifically, the all-solid-state lithium-ion battery includes the negative electrode provided by the third aspect.

[0036] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0037] The present invention utilizes a melting reaction method to convert silicon, SnS 2 As well as the metallic lithium as a reaction bridge, the uniform assembly forms a Li x Sn-Li 2 S is a three-dimensional skeleton, Li y Si active material is filled into the 3D active material of negative electrode in the pores of 3D framework. x Sn-Li 2 S three-dimensional skeleton as Li + Fast transmission channel, can be Li y Si quickly provides Li + , making the material show excellent rate performance. x Sn-Li 2The S three-dimensional skeleton can also buffer Li y The volume expansion and contraction of Si during the process of lithium insertion and delithiation ensures the integrity of the electrode structure. At the same time, because silicon has been partially lithiated into Li y Si, its volume change is relatively reduced, so the all-solid-state lithium-ion battery assembled with this three-dimensional negative electrode active material has excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a rate performance diagram of the all-solid-state lithium-ion battery composed of Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0040] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0041] Example 1

[0042] A three-dimensional negative electrode active material and a preparation method thereof.

[0043] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 3.02 Sn-Li 2 S and Li 2.92 Si composition; Li 2.92 Si is attached to the three-dimensional framework Li 3.02 Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 3.02 Sn-Li 2 S in Li 3.02 Sn and Li 2 The mass ratio of S is 1.52:1. The particle size of the three-dimensional negative electrode active material is 24.46 μm and the specific surface area is 5.86 m 2 / g.

[0044] The specific preparation method is as follows:

[0045] In an argon atmosphere, 0.7 g of metallic lithium was weighed into a crucible and the temperature was raised to 300 °C for melting and liquefaction. Then 1 g of SnS 2 Add to the melt and stir for 10 min to form SnS 2The melt is uniformly mixed with metallic lithium, and then 1g of 30nm silicon is added into it. The melt will quickly dry and react. The sample is tumbled and mixed for 10 minutes. After the sample is cooled to room temperature, it is ground and crushed to obtain a three-dimensional negative electrode active material.

[0046] Example 2

[0047] A three-dimensional negative electrode active material and a preparation method thereof.

[0048] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 3.19 Sn-Li 2 S and Li 3.01 Si composition; Li 3.01 Si is attached to the three-dimensional framework Li 3.19 Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 3.19 Sn-Li 2 S in Li 3.19 Sn and Li 2 The mass ratio of S is 1.532:1. The particle size of the three-dimensional negative electrode active material is 27.56 μm and the specific surface area is 4.29 m 2 / g.

[0049] The specific preparation method is different from that of Example 1 in that SnS 2 The mass is 0.8g.

[0050] Example 3

[0051] A three-dimensional negative electrode active material and a preparation method thereof.

[0052] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 2.71 Sn-Li 2 S and Li 2.59 Si composition; Li 2.59 Si is attached to the three-dimensional framework Li 2.71 Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 2.71 Sn-Li 2 S in Li 2.71 Sn and Li 2 The mass ratio of S is 1.496:1. The particle size of the three-dimensional negative electrode active material is 28.43 μm and the specific surface area is 5.19 m 2 / g.

[0053] The specific preparation method is different from that of Example 1 in that SnS 2 The mass is 1.5g.

[0054] Example 4

[0055] A three-dimensional negative electrode active material and a preparation method thereof.

[0056] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 2.91 Sn-Li 2 S and Li 2.78 Si composition; Li 2.78 Si is attached to the three-dimensional framework Li 2.91 Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 2.91 Sn-Li 2 S in Li 2.78 Sn and Li 2 The mass ratio of S is 1.511:1. The particle size of the three-dimensional negative electrode active material is 24.17 μm and the specific surface area is 6.24 m 2 / g.

[0057] The specific preparation method is different from that of Example 1 in that the mass of 30 nm silicon is 1.2 g.

[0058] Example 5

[0059] A three-dimensional negative electrode active material and a preparation method thereof.

[0060] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 3.05 Sn-Li 2 S and Li 2.89 Si composition; Li 2.89 Si is attached to the three-dimensional framework Li 3.05 Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 3.05 Sn-Li 2 S in Li 3.05 Sn and Li 2 The mass ratio of S is 1.522:1. The particle size of the three-dimensional negative electrode active material is 28.35 μm and the specific surface area is 5.13 m 2 / g.

[0061] The specific preparation method is different from that of Example 1 in that the particle size of silicon is 100 nm.

[0062] Comparative Example 1

[0063] A three-dimensional negative electrode active material and a preparation method thereof.

[0064] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 3.85 Sn-Li 2 S and Li 3.0 Si composition; Li 3.0 Si is attached to the three-dimensional framework Li 3.85Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 3.85 Sn-Li 2 S in Li 3.85 Sn and Li 2 The mass ratio of S is 1.582:1. The particle size of the three-dimensional negative electrode active material is 21.58 μm and the specific surface area is 12.76 m 2 / g.

[0065] The specific preparation method is different from that of Example 1 in that SnS 2 The mass is 0.3g.

[0066] Comparative Example 2

[0067] A three-dimensional negative electrode active material and a preparation method thereof.

[0068] Three-dimensional negative electrode active material: composed of three-dimensional framework Li 3.97 Sn-Li 2 S and Li 1.2 Si composition; Li 1.2 Si is attached to the three-dimensional framework Li 3.97 Sn-Li 2 On the pores of S, the three-dimensional skeleton Li 3.97 Sn-Li 2 S in Li 3.97 Sn and Li 2 The mass ratio of S is 1.591:1. The particle size of the three-dimensional negative electrode active material is 17.28 μm and the specific surface area is 21.08 m 2 / g.

[0069] The specific preparation method is different from that of Example 1 in that the mass of 30 nm silicon is 2 g.

[0070] Comparative Example 3

[0071] A negative electrode active material.

[0072] The negative electrode active material is 30nm silicon, and the silicon is not processed in any way.

[0073] Electrochemical performance testing:

[0074] The negative electrode active materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were mixed with LiP 6 S 5 Cl, vapor-grown carbon fiber (VGCF), and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 60:37:2:1 to form a composite negative electrode, and a negative electrode sheet of appropriate size was obtained through a roller pressing and slicing process. The negative electrode sheet was placed in a polyetheretherketone tube with a diameter of 10 mm, and then 100 mg of LiP 6 S5 Cl was added into the tube, which was pressed into shape at a pressure of 30 MPa and tightly contacted with the negative electrode sheet. Finally, an indium sheet and a lithium sheet were added to the other side of the solid electrolyte and pressed into shape at a pressure of 4 tons to prepare an all-solid-state lithium-ion battery with a three-layer structure (composite negative electrode / solid electrolyte / Li-In alloy).

[0075] 1. The test method of the second cycle discharge specific capacity is: constant current discharge at 0.5C at 60°C; the calculation formula of 50 cycle specific capacity retention rate (%) is: 50 cycle specific capacity retention rate = (50th cycle discharge specific capacity / second cycle discharge specific capacity) × 100%. The test results are shown in Table 1.

[0076] Table 1 The second cycle discharge specific capacity and 50 cycle specific capacity retention rate of all-solid-state lithium-ion batteries composed of Examples 1 to 5 and Comparative Examples 1 to 3

[0077] Second cycle discharge capacity (mAh / g) 50-cycle specific capacity retention rate (%) Example 1 2579.18 98.12 Example 2 2489.27 97.25 Example 3 2561.87 97.59 Example 4 2591.14 98.01 Example 5 2846.12 96.49 Comparative Example 1 2942.18 56.51 Comparative Example 2 3218.43 63.98 Comparative Example 3 3346.18 59.85

[0078] As can be seen from Table 1, the 50-cycle specific capacity retention rates of the all-solid-state lithium-ion batteries composed of Examples 1 to 5 of the present invention are all higher than those of Comparative Examples 1 to 3, indicating that the all-solid-state lithium-ion batteries composed of Examples 1 to 5 of the present invention have higher cycle stability.

[0079] 2. Rate performance test conditions: Charge and discharge tests were performed at 60°C with currents of 0.1C and 0.5C and a cut-off voltage of 2 to 4.2V. The battery was tested under a pressure of 25MPa. The results are as follows: Figure 1 shown.

[0080] from Figure 1 It can be seen that the all-solid-state lithium-ion battery composed of Example 1 exhibits excellent cycle stability. It can still maintain a specific capacity of 2313.66 mAh / g after 50 cycles, and the capacity retention rate is as high as 98.12%. This is attributed to its three-dimensional skeleton. The silicon-lithium alloy is attached in its gaps. The three-dimensional skeleton can buffer the volume expansion of the silicon negative electrode during the charging and discharging process. Therefore, the structural change of the negative electrode sheet is lower and can withstand more cycles and remain stable.

[0081] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.

Claims

1. A three-dimensional negative electrode active material, characterized in that: Including three-dimensional skeleton Li x Sn-Li2S and Li y Si, where 2≤x≤4.4, 1≤y≤4.4; The Li y Si is attached to the three-dimensional framework Li x On Sn-Li2S.

2. The three-dimensional negative electrode active material according to claim 1, characterized in that: The three-dimensional framework Li x Li in Sn-Li2S x The mass ratio of Sn to Li2S is (1~3):(1~2).

3. The three-dimensional negative electrode active material according to claim 1, characterized in that: The particle size of the three-dimensional negative electrode active material is 1 to 30 μm, and the specific surface area is 1 to 10 m 2 / g.

4. The method for preparing a three-dimensional negative electrode active material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The metal lithium is melted and liquefied, SnS2 is added, stirred, and then silicon is added, stirred, and refined after cooling to obtain the three-dimensional negative electrode active material.

5. The preparation method according to claim 4, characterized in that: The mass ratio of SnS2 to metallic lithium is (1-10):

1.

6. The preparation method according to claim 4, characterized in that: The mass ratio of silicon to SnS2 is 1:(0.6-5).

7. The preparation method according to claim 4, characterized in that: The temperature of the melt liquefaction is 180-580°C.

8. The preparation method according to claim 4, characterized in that: The particle size of the silicon is 10 to 1000 nm.

9. A negative electrode, characterized in that The negative electrode comprises the three-dimensional negative electrode active material according to any one of claims 1 to 3.

10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the negative electrode according to claim 9.